ANSWER
![g(x) = {(x + 5)}^{3} + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%7B%28x%20%2B%205%29%7D%5E%7B3%7D%20%20%2B%204)
EXPLANATION
Given the parent function:
![f(x) = {x}^{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%7Bx%7D%5E%7B3%7D%20)
If we shift the graph of f(x), 5 units to the left, then the new rule is
![x \to \: {(x + 5)}^{3}](https://tex.z-dn.net/?f=x%20%5Cto%20%5C%3A%20%20%7B%28x%20%2B%205%29%7D%5E%7B3%7D%20)
If we again, shift this graph upward by 4 units, then the completely transformed function will have the rule,
![x \to \: {(x + 5)}^{3} + 4](https://tex.z-dn.net/?f=x%20%5Cto%20%5C%3A%20%20%7B%28x%20%2B%205%29%7D%5E%7B3%7D%20%20%2B%204)
Or
![g(x) = {(x + 5)}^{3} + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%7B%28x%20%2B%205%29%7D%5E%7B3%7D%20%20%2B%204)
I think it's need to be a graph right?
Fr we need the measurements to do the work bro
Question: What is 96 multiplied by 72.
Answer:6912
Steps:Multiple 96 x 72.
Answer:
8
Step-by-step explanation:
i did 24 divided by 3
hope this helps
-mercury